Diagnostic Aids in Temporomandibular Joint Disorders - Hassan, S. Shahid (Jaypee Brothers Medical Publishers, 2014)
The study of Diagnostic Aids in Temporomandibular Joint Disorders has been a topic of interest in Oral and Maxillofacial Surgery field for many years. The topic has proved to be quite complex and complicated. Tremendous interest in this area accompanied by lack of complete knowledge has stimulated numerous concepts, theories and diagnostic methods. It is to present a logical and practical approach to the Diagnostic Aids in TMJ Disorders. The book contains 15 chapters and at last authentic bibliography is given. The intent of this text is to develop an understanding and rational approach to the diagnostic aids in TMJ disorders.